Listening as—might - Khodyreva, Anastasia (Finland, 2025)
In the recent neoliberal politico-theoretical discourses, listening has become a buzzword alongside “relational,” “care,” and “togetherness.” Simultaneously, critical day-to-day practicing of these notions remains in urgent demand, specifically directed at those social groups that live in structural privilege which entitles them to shield themselves from all the intersectionally vulnerable, screaming, perpetually and violently silenced voices. In this context, (non-aural) listening principles might (still) need to be attended to. Relatedly, the following offering is a found poem that looks for some of these principles in the feminist new materialist and musicological work of Taru Leppänen, who has been striving to listen better, to listen well.